A Fish in the Water : A Memoir - Llosa, Mario Vargas (London Faber and Faber, 1994)
The celebrated Peruvian novelist, Mario Vargas Llosa, gives an account of his ultimately unsuccessful attempt to run his country, and of his childhood and career.
Keywords: Politics and Government